Embryonic exposure to benzo(a)pyrene inhibits reproductive capability in adult female zebrafish and correlation with DNA methylation. (September 2018) - Gao, Dongxu; Lin, Jing; Ou, Kunlin; Chen, Ying; Li, Hongbin; Dai, Qinhua; Yu, Zhenni; Zuo, Zhenghong; Wang, Chonggang
Abstract: This study was conducted to investigate the effects of embryonic short-term exposure to benzo(a)pyrene (BaP), a model polycyclic aromatic hydrocarbon, on ovarian development and reproductive capability in adult female zebrafish. In 1-year-old fish after embryonic exposure to BaP for 96 h, the gonadosomatic indices and the percentage of mature oocytes were significantly decreased in the 0.5, 5 and 50 nmol/L treatments. The spawned egg number, the fertilization rate and the hatching success were significantly reduced, while the malformation rate of the F1 unexposed larvae were increased. The mRNA levels of follicle-stimulating hormone, luteinizing hormone, ovarian cytochrome P450 aromatase cyp19a1a and cyp19b, estrogen receptor esr1 and esr2, and hepatic vitellogenin vtg1 and vtg2 genes, were down-regulated in adult female zebrafish that were exposed to BaP during embryonic stage. Both 17β-estradiol and testosterone levels were reduced in the ovary of adult females. The methylation levels of the gonadotropin releasing hormone (GnRH) gene gnrh3 were significantly increased in the adult zebrafish brain, and those of the GnRH receptor gene gnrhr3 were elevated both in the larvae exposed to BaP and in the adult brain, which might cause the down-regulation of the mRNA levels of gnrh3 and gnrhr3 . This epigenetic change caused by embryonic exposure to BaP might be a reason for physiological changes along the brain–pituitary–gonad axis. These results suggest that short-term exposure in early life should be included and evaluated in any risk assessment of pollutant exposure to the reproductive health of fish. Graphical abstract: Image 1 Highlights: Embryonic exposure to BaP suppressed the ovarian development and reproductive capability in adult female zebrafish. Embryonic exposure to BaP down-regulated the mRNA levels of genes in the brain–pituitary–gonad axis and liver. The methylation levels of gnrh3 were significantly elevated in the adult zebrafish brain. The methylation levels of gnrhr3 were elevated both in the F0 larvae and in the adult brain. The mRNA levels of gnrh3 and gnrhr3 were down-regulated. Abstract : Reduced reproductive capability in adult females resulted from embryonic exposure to BaP may be correlated with the hypermethylation of gnrh3 and gnrhr3 .